2017
DOI: 10.1038/tp.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

Progress and roadblocks in the search for brain-based biomarkers of autism and attention-deficit/hyperactivity disorder

Abstract: Children with neurodevelopmental disorders benefit most from early interventions and treatments. The development and validation of brain-based biomarkers to aid in objective diagnosis can facilitate this important clinical aim. The objective of this review is to provide an overview of current progress in the use of neuroimaging to identify brain-based biomarkers for autism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD), two prevalent neurodevelopmental disorders. We summarize empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 91 publications
(70 reference statements)
3
109
0
1
Order By: Relevance
“…Finally, a disrupted interplay between the DAN-SN-DN has been consistently observed in autism (e.g. Uddin et al, 2017) and considerable efforts aim at evaluating the therapeutic potential of intranasal OXT for alleviating symptoms of autism (Guastella and Hickie, 2016;Keech et al, 2018). Thus, in line with previous studies (Bethlehem et al, 2017;Scheele et al, 2014) associations between OXT effects and individual variations in autistic traits were additionally explored.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Finally, a disrupted interplay between the DAN-SN-DN has been consistently observed in autism (e.g. Uddin et al, 2017) and considerable efforts aim at evaluating the therapeutic potential of intranasal OXT for alleviating symptoms of autism (Guastella and Hickie, 2016;Keech et al, 2018). Thus, in line with previous studies (Bethlehem et al, 2017;Scheele et al, 2014) associations between OXT effects and individual variations in autistic traits were additionally explored.…”
Section: Introductionmentioning
confidence: 87%
“…In line with prior work reporting that OXT's effect on intrinsic connectivity (Bethlehem et al, 2017) and social processing related neural activity vary as a function of autistic traits, exploratory analysis revealed positive associations between levels of autistic traits and SN-DN (i.e., accSN-pvDN, accSN-pdDN, inSN-pdDN) connectivity following OXT, but not PLC. Both, ACC and AI core regions of the SN have repeatedly been associated with ASD (Anderson et al, 2011;Uddin et al, 2013) and overconnectivity between these networks, possibly reflecting deficient segregation (Rudie et al, 2012), has been considered as promising diagnostic and predictive ASD marker (Hogeveen et al, 2018;Uddin et al, 2017). Initial clinical trials in ASD demonstrated attenuated social-cognitive deficits in ASD following OXT that were mediated by modulatory effects on AI and ACC activity (Andari et al, 2016;Aoki et al, 2014;Watanabe et al, 2015).…”
Section: Association Between Dn-sn Connectivity and Autism Traitsmentioning
confidence: 99%
“…Specifically, studies of individuals with ADHD report reduced segregation of DMN-FPN networks in children, adolescents, and adults 54,55 , but results from withinnetwork connectivity studies are less coherent. For example, both hyperconnectivity 16 and hypoconnectivity 18 techniques, which suggested that heterogeneity within and between disorders may be limiting researchers' (and machines') ability to distinguish disorders based on neurobiology 57 . Two factors may be contributing to the limited neurobiological separability of ASD and ADHD categories: high within-category heterogeneity and high between-category similarity.…”
Section: Discussionmentioning
confidence: 99%
“…This review included other existing methods proposed to diagnose ADHD, that were not covered in the former systematic review. To make the indirect comparison possible, this in-house scoping review included only diagnostic accuracy studies that reported the chosen metrics of diagnostic for methods based on; electroencephalography and eventrelated potentials (Marcano et al, 2017;Loo et al, 2016;Snyder et al, 2015;Mohammadi et al, 2016;Gloss et al, 2016;Biederman et al, 2017;Gamma and Kara, 2016;Marcano et al, 2018;Manouilenko et al, 2017), structural and functional neuroimaging (Iannaccone et al, 2015;Rangarajan et al, 2014;de Celis Alonso et al, 2017;Qureshi et al, 2017;Serrallach et al, 2016;Hasaneen et al, 2017;Tan et al, 2017b;Uddin et al, 2017), simulated virtual reality and computer games (Negut et al, 2017(Negut et al, , 2016Berger et al, 2017;Faraone et al, 2016), and peripheral biochemical markers (Faraone et al, 2014;Scassellati and Bonvicini, 2015;Scassellati et al, 2012;Thome et al, 2012). According with this complementary "scoping review", the method presented in this research, seems to outperforms all the diagnostic accuracy metrics reported in the trials scrutinised in the aforementioned review.…”
Section: The Inferential Activity (Both At Sensory-motor and Represenmentioning
confidence: 99%